The Pivotal Role of Nursing Leadership in Hospital Health Management and Quality Improvement Initiatives: A Comprehensive Review - Al-Mawlid, Hana Eid Ali; Salha Mohmmed Al Garni; Saeed Ali S Alzahrani; Mansour Bakheet Alshanbari; Rawan Mansour Ali Sarhan; Seham Mohammad Abdoalrahman Alhawsawi; Khadijah Ahmad Abdallh bin Zarah; Amnah Hamood Althalabi (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The healthcare context in which nurses practise is increasingly complex, with financial pressures and a continued demand for high-quality, safe patient care. It is in this context that nursing leadership can no longer be regarded solely as a supportive discipline but as integral to organizational performance. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim: <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">To synthesize and critically analyze existing literature on the role of nursing leadership in health management and quality improvement initiatives within a hospital. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A systematic narrative review methodology was adopted. A comprehensive search of electronic databases for peer-reviewed literature between the years 2000 and 2024 was carried out. Keywords included "nursing leadership," "quality improvement," "patient safety," "health management," "transformational leadership," and "hospital." Studies that met the review inclusion criteria were thematically analyzed. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results: <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Several pivotal nursing leadership roles were identified through the analysis, including: 1) establishing a safety culture and continuous improvement; 2) implementing and sustaining evidence-based practice (EBP); 3) applying strategic leadership styles, notably transformational and resonant leadership; 4) optimizing human resources management, including staffing and retention; and 5) using data related to performance monitoring. <span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; color: #0f1115; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Nursing leadership is an indispensable part of effective hospital health management. Evidence clearly indicates that strong, strategic, and supportive nursing leadership development is not an optional luxury but a core essential for the pursuit of excellence in patient care and the long-term sustainability of healthcare organizations.